National spatial data infrastructure collaboration for the Kingdom of Saudi Arabia - Alshehri, Saad Abdulrahman F. (2011)
Spatial data is a vital national resource necessary for a country’s efficient and sustainable economic, social and environmental development, and so must be properly developed and managed. In the Kingdom of Saudi Arabia (KSA), there is lack of knowledge and no clear framework describing the optimal way for stakeholders, users, providers or administrators, to collaborate effectively in establishing a National Spatial Data Infrastructure (NSDI). Moreover, the complex, multi-layer and multi-jurisdiction system of government leads to competing interests and mandates in coordinating spatial activity.